Odpowiedź :
Odpowiedź:
4x + 8 = 12
4x = 12 - 8
4x = 4 /:4
x = 1
-3x - 5 = 4
-3x = 4 + 5
-3x = 9 /: -3
x = -3
9 - 2 = 21
(źle zapisane)
1,5 + 3x = 4,5
3x = 4,5 - 1,5
3x = 3 /:3
x = 1
-2x + 7 = 7
-2x = 7 - 7
-2x = 0
x = 0
4 - 1 = 7
(źle zapisane)
5x + 2 = 12
5x = 12 - 2
5x = 10 /:5
x = 2
-8x - 3 = 0
-8x = 0 + 3
-8x = 3 /: -8
x = - 3/8 (ułamek)
Proszę o komentarz poprawiający 2 działania aby odpowiedź była kompletna.
4x + 8 = 12
4x = 12 - 8
4x = 4
x = 4/4
x = 1
-3x - 5 = 4
-3x = 4 + 5
-3x = 9
x = 9/-3
x = -3
9 - 2 = 21 ?
1,5 + 3x = 4,5
3x = 4.5 - 1.5
3x = 3
x = 3/3
x = 1
-2x + 7 = 7
-2x = 7 - 7
-2x = 0
x = 0
4 - 1 = 7 ?
5x + 2 = 12
5x = 12 - 2
5x = 10
x = 10/5
x = 2
-8x - 3 = 0
-8x = 3
x = 3/-8
x = - 3/8